Molecular Cascades That Build and Connect Auditory Neurons from Hair Cells to the Auditory Cortex - Yamoah, Ebenezer N; Pavlinkova, Gabriela; Fritzsch, Bernd (Journal of experimental neurology, 2025)
Understanding the development of the auditory system is crucial for uncovering the molecular origins of hearing and its related disorders. During this development, spiral ganglion neurons extend peripheral fibers to cochlear hair cells and central projections to the cochlear nuclei, setting up a tonotopic map that connects the ear to the brainstem, enabling frequency-specific sound perception. This sensory information is then integrated bilaterally through a relay involving the superior olivary complex, lateral lemniscus, inferior colliculus, medial geniculate body, and the auditory cortex. While anatomical connectivity has been well-documented, recent advancements have revealed gene regulatory networks that coordinate the specification, differentiation, and connectivity of auditory neurons. In this review, we examine the molecular cascades guiding auditory system development, emphasizing transcriptional hierarchies and lineage determinants. Insights into these mechanisms enhance our understanding of auditory circuit formation and provide a critical foundation for therapeutic strategies aimed at addressing congenital and acquired hearing loss.
Keywords: Brainstem; Cochlear hair cells; Cochlear nuclei; Auditory cortex; Genetic basis; Spiral ganglion neurons